Intimacy Over Power Developing Learners’ Motivation: A Study At ESP Class - Arni Arsyad Sultan (Institut Agama Islam Negeri Palopo, 2023)
This current research attempts to show that intimacy relationship of student to student has a bigger influence rather than power relationship of lecturer – student to raise motivation in learning process. Certainly, the so-called power in social variable has directly affected in lecturer-student relationship even though the influence is not as big as intimacy relationship has. The relationship between student to student is much easier to communicate for their academic business and even for personal range of problem. It is actually a very potential aspect to raise their motivation in learning. Before collecting primary data, the researcher investigates preliminary data by applying participant observer. After gaining it, the researcher collects primary data through interview. 63 students from English for Specific Purposes class on the fifth semester of English education department at IAIN Bone are asked. Finally, the data are explained by using descriptive qualitative analysis. As a conclusion, intimacy factor among learners is more influential in raising motivation of language learning over power factor held between lecturer and learners. Feeling pleasant to communicate about learner’ incomprehension to their friends, supporting, co-working, and even pushing to strive or to finish the duty become the implementation of the friendship role in intimacy among learners. On the other hand, the respondents could feel clumsy, nervous, shy, or disinclined to express what they have in mind to the lecturer. It is, of course, ultimately affecting the way learner communicates to their lecturer.